Determination of the critical combination in the interval training and application to a model to prescribe the training menu - Kitajima, M.; Wakayoshi, K.; Takahashi, A.; Takahashi, S.; Nomura, T.; Ogita, F. (Japanese Journal of Sciences in Swimming and Water Exercise, 2006)
The purpose of this study was to determine the critical combination of all four elements which expressed the threshold of fatigue in interval training by using the critical swimming velocity that was an effective index when we set training strength, and to make a model that we could use as an indicator when we prescribed the training menu that accepted an individual. Only for 50m at repeated distance, we set a different rest time in three phases of different swimming velocity each and performed a test to let subjects repeat exercise up to fatigue. In addition, we measured the maximum repetitions that could repeat exercise. As a result, it became clear that the maximum repetitions that could repeat interval training without reaching fatigue in a certain swimming velocity was in proportion to the total rest time. And then, we were able to see the relations with the repetitions and the rest time in three phases of different swimming velocity. Furthermore, we were able to get relations with the rest time and the swimming velocity which expressed the threshold of fatigue in the arbitrary repetitions by fixing the repetitions. It was concluded that we were able to determine the critical combination from the above-mentioned by this study.